2011
DOI: 10.1186/1745-6215-12-99
|View full text |Cite
|
Sign up to set email alerts
|

A pseudo-randomised clinical trial of in situ gels of fluconazole for the treatment of oropharngeal candidiasis

Abstract: BackgroundOropharyngeal candidasis is a common opportunistic infection seen in immunocompromised patients. Fluconazole has a broad spectrum antifungal activity including a wide variety of candida species. Aim of the present investigation was to formulate and find out the relative efficacy of in situ gels of fluconazole.MethodThe in situ gels were prepared using polymers which exhibited sol-to-gel phase transition due to change in specific physico-chemical parameters, such as ion triggered system using gellan g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…cultures from swabs taken at the same sites used before treatment. 11 For the first approach, the evaluation was rated as better (minimal signs and symptoms with no residual visible candidiasis), unchanged, and worse. Following the initial visit, patients were clinically examined every 2 days.…”
Section: Methodsmentioning
confidence: 99%
“…cultures from swabs taken at the same sites used before treatment. 11 For the first approach, the evaluation was rated as better (minimal signs and symptoms with no residual visible candidiasis), unchanged, and worse. Following the initial visit, patients were clinically examined every 2 days.…”
Section: Methodsmentioning
confidence: 99%
“…A single-dose regimen of 750 mg fluconazole has been shown to be as effective as a standard 14-day regimen (Hamza et al, 2008). In addition, in situ fluconazole gel demonstrated effectiveness compared to daily 100 mg fluconazole tablets (Nairy et al, 2011). However, prolonged use of fluconazole increases the risk of developing azole-resistant C. albicans (Patton et al, 2001).…”
Section: Antifungal Drug Resistancementioning
confidence: 99%
“…Recently, a single‐dose regimen of 750 mg fluconazole has been shown to be as effective as a standard 14‐day regimen in achieving clinical and mycological cure in the treatment for OC in patients with HIV infection (Hamza et al , ). A small trial of in situ fluconazole gel demonstrated effectiveness compared to daily 100 mg fluconazole tablets (Nairy et al , ).…”
Section: Is There Any Novelty In the Treatment Of Oral Manifestationsmentioning
confidence: 99%